Internalisasi, Interkoneksi, Integrasi: Kepemimpinan Apostolik Paulus Dalam Misi Menurut Roma 15-16 - Paulus Dimas Prabowo (JURNAL TRANSFORMASI: Jurnal Teologi dan Kepemimpinan, 2023)
The success of a mission's work also depends on the leadership that oversees it. This expression is not just a figment of the imagination, but a fact that has been written down by history. Medieval church missions are an example, providing some evidence that the erroneous actions of mission leaders hampered development and even halted it. Mission activities need to reflect Biblical truth, especially the apostolic leadership of the apostles. Among the several apostles, one who can be used as a patron is Paul in Romans 15-16. These two articles have an integral structure that is able to show Paul's apostolic leadership pattern, especially in efforts to fulfill his divine mission to all nations. Through a thematic analysis approach by paying attention to structural, grammatical, historical and contextual aspects, several points were obtained regarding Paul's apostolic leadership pattern, including uniting churches of various nationalities, carrying out missions for all nations, preaching the gospel, reaching new areas, mobilizing social missions for those in need, encouraging prayer support, establishing partnerships across diverse ethnic groups and social strata, seeking to mature the congregation, and serving in a Christ-centered manner. These points can be categorized into internalization, interconnection and integration aspects.